Розвиток методичної компетентності вчителя математики як педагогічна проблема - Михайленко Любов (Бердянський державний педагогічний університет, 2020)
У статті висвітлено проблеми розвитку методичної компетентності вчителів математики. Проведено аналіз, систематизацію теоретичних положень, розкритих в офіційних документах, науковій та навчально-методичній літературі; узагальнення власного педагогічного досвіду, а також практики щодо розвитку методичної компетентності вчителя математики. Важливою для ефективності реформування загальної середньої освіти є перепідготовка вчителів до реалізації основних напрямів нової освітньої реформи. Вважаємо, що ефективність перебудови шкільної математичної освіти значно залежить від реформування системи підвищення кваліфікації вчителя математики. Має змінитися не тільки зміст, а й технології професійного зростання вчителя нового покоління в педагогічних закладах вищої освіти. Методичну компетентність вважаємо однією з основних складових професійної компетентності вчителя математики. У статті аргументовано позитивний вплив партнерської взаємодії педагогічного університету та школи на умови методичного розвитку вчителів математики. Важливо розробити типову освітню програму організації і проведення підвищення кваліфікації педагогічних працівників закладами вищої педагогічної освіти та чітко визначити програмні результати навчання – знання, уміння, навички, способи мислення, погляди, цінності, інші особисті якості учителів математики, набуті в процесі фахової підготовки, які можна ідентифікувати, спланувати, оцінити і виміряти та які вчитель здатен продемонструвати після завершення освітньої програми або окремих її освітніх компонентів. Розробка освітніх програм підвищення кваліфікації вчителів доцільна не тільки за спеціальностями, а за міждисциплінарними програмами, що є більш гнучкими та налаштованими на сучасні потреби шкільної освіти. Зазначено необхідність постійного оновлення змісту курсів підвищення кваліфікації вчителів математики для задоволення швидкозмінних освітніх потреб в розвитку методичних компетентностей на всіх рівнях його професійної діяльності.
Development of methodical competence of a math teacher as a pedagogical problem
The problems of development of methodical competence of mathematics teachers are covered in the article. The analysis, generalization, systematization of theoretical provisions revealed in official documents, scientific and educational-methodical literature are carried out; generalization of own pedagogical experience, as well as analysis of practical experience in the development of methodological competence of the teacher of mathematics. Important for the efficiency of reforming general secondary education is the retraining of working teachers to implement the main directions of the new educational reform. We believe that the effectiveness of reforming school mathematics education is highly dependent on reforming the system of advanced training of mathematics teachers. Not only the content needs to change, but the technologies of professional growth of the next generation of teachers in higher education pedagogical institutions need to be improved and updated. We consider methodical competence one of the main components of the professional competence of a working mathematics teacher. The positive influence of partnership of pedagogical university and school on conditions of methodical development of working mathematics teachers is argued in the article. It is important to develop a typical educational program for organizing and improving the qualification of pedagogical staff in higher education institutions and to clearly define program learning outcomes – knowledge, skills, ways of thinking, views, values, other personal qualities of mathematics teachers, which can be acquired in the process, identify, plan, evaluate and measure and which the teacher is able to demonstrate after completing the educational program or its individual educational components. The development of teacher education programs is advisable not for specialties but for interdisciplinary programs that are more flexible and tailored to the contemporary needs of school education. The necessity of constant updating of the content of the advanced training courses of mathematics teachers to meet the rapidly changing educational needs of the teacher in the development of methodological competences, at all levels of his professional activity, is noted.